تأثير ترابط القناة في النموذج Weibull-Gamma على أداء خوارزمية اختيار الهوائيات في النظام MIMO STBC - غدير ماضي (Tishreen University, 2018)
Multiple antennas systems MIMO have proven their ability to improve the performance of wireless communication in terms of increasing data rate and reducing bit error rate, making it a key technique of existing and future communications systems. The antenna selection algorithm in MIMO systems permits to select a subset of the antennas available at the transmitter depending on a certain criteria. This has contributed to the deployment of space time block code STBC in MIMO systems which have more than two antennas at the transmitter. The antenna selection algorithm performance is influenced by the model and characteristics of the MIMO wireless communication channel. Therefore, this research deals with the effect of channel correlation on the performance of the antenna selection algorithm in MIMO STBC system assuming the Weibull-Gamma channel model recently proposed in scientific researches. The results showed the efficiency of application of the antenna selection algorithm in MIMO STBC system. It also showed that the antenna selection algorithm could work well within a certain domain of the Weibull-Gamma channel correlation factor. أثبتت أنظمة الهوائيات المتعددة (MIMO) Multiple Input Multiple Output قدرتها على تحسين أداء الاتصال اللاسلكي من حيث زيادة معدل الإرسال وتخفيض معدل الخطأ, مما جعلها ركيزة أساسية لأنظمة الاتصالات الحالية والمستقبلية. تسمح خوارزمية اختيار الهوائيات في أنظمة MIMO باختيار مجموعة جزئية من الهوائيات المتوفرة في المرسل وذلك تبعا لمعيار محدد, الأمر الذي ساهم بانتشار تقنية الترميز المكاني الزماني STBC بشكل واسع في هذه الأنظمة التي تحوي أكثر من هوائيين في المرسل. يتأثر أداء خوارزمية اختيار الهوائيات بنموذج وخصائص قناة الاتصال اللاسلكية للنظام. لذلك يتناول هذا البحث مسألة تأثير ترابط القناة على أداء خوارزمية اختيار الهوائيات للنظام MIMO STBC بافتراض نموذج القناة المسمى Weibull-Gamma المقترح حديثا في الأبحاث العلمية. أظهرت النتائج فعالية تطبيق خوارزمية اختيار الهوائيات ضمن النظام MIMO STBC من جهة, ومن جهة أخرى إمكانية عمل خوارزمية اختيار الهوائيات بشكل جيد ضمن مجال معين لعامل ترابط القناة Weibull-Gamma.